New wave science fiction and the exhaustion of the utopian/distopian dialectic - Steble, Janez (ELOPE (Ljubljana), 2011)
The paper explores the development of the utopian and dystopian literature in the experimental and prolific period of New Wave science fiction. The genre literature of the period chiefly expressed the dissolutions of the universe, society, and identity through its formal literary devices and subject-matter, thus making it easy to arrive at the conclusion that the many SF works of J. G. Ballard's post-apocalyptic narratives, for example, exhausted and bankrupted the utopian/dystopian dialectic. However, the article provides textual evidence from one of the most prominent authors of the New Wave and the theoretical basis to suggest the contrary, namely that the categories of utopia and dystopia had by that time reached a level of transformation unprecedented in the history of the genre. Furthermore, the paper explores the inherent qualities science fiction shares with utopian literature, and suggests that the dialogism of the science fiction novel, especially that of the New Wave, has brought about the revival of utopia and rediscovered its potential.
Keywords: angleška književnost; English literature; entropija; entropy; heterotopia; heterotopija; Postmodernism; postmodernizem; prevrednotenje; science fiction; transvaluation; utopia; utopija; znanstvena fantastika